2015
DOI: 10.1371/journal.pone.0126858
|View full text |Cite
|
Sign up to set email alerts
|

Management of Type 2 Diabetes Mellitus through Telemedicine

Abstract: BackgroundType 2 diabetes mellitus T2DM has a huge and growing burden on public health, whereas new care models are not implemented into clinical practice; in fact the purpose of this study was to test the effectiveness of a program of integrated care for T2DM, compared with ordinary diligence.Methods"Progetto Diabete Calabria" is a new organizational model for the management of patients with diabetes mellitus, based on General Practitioners (GPs) empowerment and the use of a web-based electronic health record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…Legget et al [11] reported high diagnostic accuracy (97%) for rheumatological conditions using real-time televisual consultation with 58% of patients expressing a preference for telemedicine consultation. Similar studies support use of telemedicine in long-term management of diabetes [12][13][14].…”
Section: Applications Of Telemedicinesupporting
confidence: 61%
“…Legget et al [11] reported high diagnostic accuracy (97%) for rheumatological conditions using real-time televisual consultation with 58% of patients expressing a preference for telemedicine consultation. Similar studies support use of telemedicine in long-term management of diabetes [12][13][14].…”
Section: Applications Of Telemedicinesupporting
confidence: 61%
“…Recently many studies indicated that mobile medical intervention tools are effective in a wide range of areas for both disease management and lifestyle changes. [4][5][6][7][8] Some studies have shown that among diverse computer-based technologies, mobile phone interventions for diabetes self-management can significantly reduce hemoglobin A1c (HbA1c) levels. 9,10 In treatment with T2D, as recommended by the Chinese Guideline for Diabetes Prevention and Treatment and from the American Diabetes Association (ADA) guideline, insulin therapy is one of the best choices for T2D patients who could not get well glucose control by at least one oral antidiabetic drug (OAD).…”
Section: Introductionmentioning
confidence: 99%
“…The intervention groups were mostly compared with a group receiving usual care [21-25,27,29,30,32,33], with a specialist outpatient and a nurse practitioner clinic [28] or in one case through general correspondence by email [31]. …”
Section: Resultsmentioning
confidence: 99%